Incidence and Prognostic Impact of DNMT3A Mutations in Korean Normal Karyotype Acute Myeloid Leukemia Patients. (11th January 2015) - Park, Sang Hyuk; Choi, Jae-Cheol; Kim, Shine Young; Yi, Jongyoun; Oh, Seung Hwan; Kim, In-Suk; Kim, Hyung-Hoi; Chang, Chulhun Ludgerus; Lee, Eun Yup; Song, Moo-Kon; Shin, Ho-Jin; Chung, Joo Seop
Abstract : Background . DNA methyltransferase 3A ( DNMT3A ) mutation was recently introduced as a prognostic indicator in normal karyotype (NK) AML and we evaluated the incidence and prognostic impact of DNMT3A mutations in Korean NK AML patients. Methods . Total 67 NK AML patients diagnosed during the recent 10 years were enrolled. DNMT3A mutations were analyzed by direct sequencing and categorized into nonsynonymous variations (NSV), deleterious mutations (DM), and R882 mutation based on in silico analysis results. Clinical features and prognosis were compared with respect to DNMT3A mutation status. Results . Three novel (I158M, K219V, and E177V) and two known (R736H and R882H) NSVs were identified and the latter three were predicted as DMs. DNMT3A NSVs, DMs, and R882 mutation were identified in 14.9%–17.9%, 10.3%–10.4%, and 7.5% of patients, respectively. DNMT3A mutations were frequently detected in FLT3 ITD mutated patients ( P = 0.054, 0.071, and 0.071 in NSV, DMs, and R882 mutation, resp.) but did not affect clinical features and prognosis significantly. Conclusions . Incidences of DNMT3A NSVs, DMs, and R882 mutation are 14.9%–17.9%, 10.3%–10.4%, and 7.5%, respectively, in Korean NK AML patients. DNMT3A mutations are associated with FLT3 ITD mutations but do not affect clinical outcome significantly in Korean NK AML patients.